2023
DOI: 10.3389/fnins.2023.1180434
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging studies of acupuncture at ST36: a coordinate-based meta-analysis

Abstract: BackgroundFunctional magnetic resonance imaging (fMRI) has been widely used to investigate the brain effect of acupuncture point Stomach 36 (ST36, Zusanli). However, inconsistent results have hindered our understanding of the neural mechanisms of acupuncture at ST36.ObjectiveTo perform a meta-analysis of fMRI studies on acupuncture at ST36 to assess the brain atlas of acupuncture at ST36 from available studies.MethodBased on a preregistered protocol in PROSPERO (CRD42019119553), a large set of databases was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…The previous brain imaging research has proven that the functional whole‐brain network architecture of healthy individuals is altered after EA intervention, which confirms the brain function related to the specificity of meridians and acupoints (Han, Jin, et al., 2020). A meta‐analysis study with ST36 showed that it was able to activate the left cerebellum, the bilateral Rolandic operculum, the right supramarginal gyrus, and the right cerebellum, and acupuncture at ST36 was primarily associated with perception and action according to functional characterizations (Zhang et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The previous brain imaging research has proven that the functional whole‐brain network architecture of healthy individuals is altered after EA intervention, which confirms the brain function related to the specificity of meridians and acupoints (Han, Jin, et al., 2020). A meta‐analysis study with ST36 showed that it was able to activate the left cerebellum, the bilateral Rolandic operculum, the right supramarginal gyrus, and the right cerebellum, and acupuncture at ST36 was primarily associated with perception and action according to functional characterizations (Zhang et al., 2023).…”
Section: Introductionmentioning
confidence: 99%